Comparison of Volatile Compounds in Two Brandies Using HS-SPME Coupled with GC-O, GC-MS and Sensory Evaluation - Zhao, Y.P.; Wang, L.; Li, J.M.; Pei, G.R.; Liu, Q.S. (South African Journal of Enology and Viticulture, 2016)
The aim of this study was to compare the volatile compounds between Changyu XO and Hennessy XO. Sensory evaluation was performed by a panel of tasters. Qualitative and semi-quantitative analysis was achieved by headspace solid phase micro-extraction (HS-SPME), coupled with gas chromatography-mass spectrometry (GCMS) and gas chromatography-olfactometry (GC-O). A total of 160 volatile compounds were identified in the two brands of brandy. Of these, 118 compounds were common to both Changyu XO and Hennessy XO; 18 compounds were specific to Changyu XO and 24 were specific to Hennessy XO. A total of 85 aroma compounds responsible for brandy flavour were identified by GC-O, of which 68 were common to both brands, while seven and ten were specific to Changyu XO and Hennessy XO, respectively. The study provided detailed information about the compounds responsible for the characteristic flavour of specific brandies. According to statistical analysis, significant differences were recorded between Changyu XO and Hennessy XO. Most volatile compounds in Changyu XO occurred at lower concentrations than those in Hennessy XO. Based on sensory evaluation analysis, the floral, alcohol and rancid aroma descriptors achieved higher scores in Changyu XO and Hennessy XO, while the lime aroma seemed specific to Hennessy XO. Herb and almond aromas were specific to Changyu XO.